Pelanggaran Etika Profesi Pada Kasus Indonesia Corruption Watch (ICW) - Dwi Urip Wardoyo; Nailah Artanti; Erika Annisa Damayanti (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study focuses on cases of violations of professional ethics at a Public Accounting Firm in Jakarta which were investigated based on reports from the Financial and Development Supervisory Agency (BPKP) who were suspected of colluding with their clients. The purpose of this study is to find out cases of violations of professional ethics investigated by Indonesia Corruption Watch (ICW). The objects in this study are nine Public Accounting Firms in Jakarta for those domiciled in Jakarta.